Synthesis and properties of light weight magnesium–cenosphere composite. Issue 9 (12th June 2016) - Nguyen, Q. B.; Sharon Nai, M. L.; Nguyen, A. S.; Seetharaman, S.; Wai Leong, E. W.; Gupta, M.
Abstract : Significantly light weight magnesium composite foams are synthesised by addition of fly ash cenosphere particles (waste from coal-fired power plants) in biocompatible pure magnesium using solidification-based disintegrated melt deposition technique. The density of the composite foams synthesised in this study approaches that of plastics- and polymer-based composites. Microstructure development of Mg/cenosphere composite foams was favourable as they exhibited better dimensional stability (reduced coefficient of thermal expansion) and remarkable improvements in tensile strengths, compressive strengths, compressive total strain and microhardness. The present study highlights the processing, microstructure and mechanical properties of Mg/cenosphere composite foams which hold great potential as light weight metal-based green materials for diverse weight critical applications spanning from engineering to biomedical sector.